A Study on Consumers Satisfaction of Double Dragon Tattooz Shop at Ahmedabad - Patel, Amit; Shukla, Prachi; Vidani, Jignesh (Contemporary Journal of Applied Sciences, 2024)
This research evaluates consumer satisfaction at the Double Dragon Tattoo Shop, Ahmedabad, in understanding how age affects customer experience. Using the analytical technique of 'quantitative analysis', it examines the way age behaves with respect to attributes such as comfort, perceptions about hygiene, staff responsiveness, and likelihood of repeat business. The findings of this research indicated that customers who are relatively older seek comfort and hygiene, which are critical to satisfaction and loyalty. The study emphasizes on communication and personalized service. The practical implications are personalization of services to each age group, hygiene standards, and a cozy atmosphere. Future research is necessary on other demographic factors and longitudinal studies to understand technology and social media impacts on consumer behavior to improve customer satisfaction and business growth in the tattoo industry